Data-driven process discovery and analysis : 6th IFIP WG 2.6 International Symposium, SIMPDA 2016, Graz, Austria, December 15-16, 2016, Revised selected papers /: 6th IFIP WG 2.6 International Symposium, SIMPDA 2016, Graz, Austria, December 15-16, 2016, Revised selected papers. (2018) - Unknown
No abstract available